Reverse strategy to locally advanced breast implant-associated anaplastic large cell lymphoma: A case report - Cappelli, Sonia; Marchesi, Francesco; Clementi, Marco; Perracchio, Letizia; Palombi, Francesca; Pelle, Fabio; Botti, Claudio; Costantini, Maurizio (Frontiers in Oncology, 2023)
Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is a rare T-cell lymphoma associated with textured breast implants. The most common presentation is a periprosthetic seroma that occurs at least 1 year after an aesthetic or reconstructive implantation, and in these cases the surgical treatment seems to be successful. More rarely BIA-ALCL presents with locally advanced mass-formed disease and a related regional lymph node involvement. In all these cases with worse prognosis, a multidisciplinary approach is required including adjuvant chemotherapy, radiation therapy and surgery. We present a clinical case of a 49-year-old woman who developed on the left side of the breast a mass-formed stage 3 BIA-ALCL 15 years after a bilateral breast augmentation with textured silicone implant. Our multidisciplinary team (MDT) scheduled the patient for a “reverse-strategy” sequential approach consisting of induction chemotherapy, hematopoietic stem cell mobilization and harvest followed by autologous stem cell transplant (ASCT). After 100 days from the stem cell transplant, the patient showed a complete pathologic response and was candidate for radical surgery. She underwent removal of both implants with total en-bloc capsulectomy. On the left site, the periprosthetic mass was also en-bloc removed. We did not perform any axillary dissection. Our surgical and hemato-oncologists teams followed the patient, every 3 months and no local or systemic recurrences were observed 24 months after surgery. This case report has demonstrated the effectiveness of neoadjuvant chemotherapy as part of a “reverse-strategy” in selected cases of advanced stage BIA-ALCL in which was not possibile to perform an immediate radical surgery. Furthermore, in our case the de-escalation strategy adopted permitted a less demolitic surgery with good functional and aesthetic results.